Appropriateness of agricultural marketing information service in Punjab, Pakistan. Issue 3 (2nd April 2020) - Yaseen, Muhammad; Ahmad, Mokbul Morshed
ABSTRACT: This article evaluates the appropriateness of the existing agricultural marketing information service (AMIS) in the Punjab province of Pakistan in terms of the accuracy of data collected, quality of the information produced, effective dissemination of information, and sustainability of the service, based on criteria developed on different indicators. Both secondary and primary data were collected through literature review, key informant interviews and focus group discussions. Qualitative analysis technique was used to discuss the appropriateness of the service. The inappropriate and weak dimensions of the service are highlighted to guide the future improvement of AMIS.